2016
DOI: 10.1016/j.exger.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sleep quality, and self-reported fatigue across the adult lifespan

Abstract: Deteriorating sleep quality and increased fatigue are common complaints of old age, and poor sleep is associated with decreased quality of life and increased mortality rates. To date, little attention has been given to the potential effects of physical activity on sleep quality and fatigue in aging. The purpose of this study was to examine the relationships between activity, sleep and fatigue across the adult lifespan. Sixty community-dwelling adults were studied; 22 younger (21–29 years), 16 middle-aged (36–6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 27 publications
3
52
3
Order By: Relevance
“…In agreement with our results, Kakinami et al observed that more time spent in sedentary activities was associated with poorer SQ in young adults. Regarding MVPA, a study in a small sample of healthy adults ≥65 years old (n = 60) showed that MVPA was associated with better SQ . Slightly in contrast, we observed (in our larger sample) no direct association between MVPA (in bouts of ≥10 minutes) and the SQ global score.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In agreement with our results, Kakinami et al observed that more time spent in sedentary activities was associated with poorer SQ in young adults. Regarding MVPA, a study in a small sample of healthy adults ≥65 years old (n = 60) showed that MVPA was associated with better SQ . Slightly in contrast, we observed (in our larger sample) no direct association between MVPA (in bouts of ≥10 minutes) and the SQ global score.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding MVPA, a study in a small sample of healthy adults ≥65 years old (n = 60) showed that MVPA was associated with better SQ. 18 Slightly in contrast, we observed (in our larger sample) no direct association between MVPA (in bouts of ≥10 minutes) and the SQ global score. Nevertheless, when…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…These findings are generally consistent with other community-based studies in adults [37] and interventions among adolescents [38]. …”
Section: Discussionsupporting
confidence: 91%